As decisões do pleno do STF : caráter vinculante na aplicação do caso concreto independentemente da edição de súmula - Amorim, João Fernando Carneiro Leão de (2014)
This work is a reflection on the interpretation and application of the law from the perspective of the principle of free conviction . The study analyzes the judge s decision considered as an act of volition, as well as the relationship between this subjective act and the objective foundations presented to justify the making of the decision. Next, I focus on judicial precedent: its analysis, classification, and ways of overcoming and distinguishing between precedents. Stare decisis in Brazil is examined, analyzed in terms of the institution and its standing to propose, modify or cancel, as well as its operationalization. Also considered is the possibility of requiring legal practitioners to respect the precedents set by the Supreme Federal Court Plenary, independently of stare decisis. Finally, the historical record in respect to precedents in the administrative process is examined, comparing to those created by the judiciary.